Hubungan Adiksi Game Online Dengan Personal Hygiene Pelajar SMK Istiqomah Muhammadiyah 4 di Samarinda - Halimah Seftiyani, Nur; Purdani, Kartika Setia; Safrudin, M. Bachtiar (LPPM Hang Tuah Pekanbaru, 2025)
Background: adolescent gamers may alter their regular approach to personal hygiene if they spend a lot of time playing video games online. Objective: The study's overarching goal is to ascertain if SMK Istiqomah Muhammadiyah 4 Samarinda students' cleanliness habits are related to their gaming addiction. Methode: a cross-sectional design was used as an approach in this writing. The sample consisted of 131 students from second grade, who met the inclusion and exclusion criteria, then the chi-square test was carried out to prove the relationship between these variables. Results: of the 131 students at SMK Istiqomah Muhammadiyah 4 Samarinda who participated in research on online game addiction, it can be concluded that there are two levels of severity: mild (61 of 131, or 44.6% of 131) and moderate (71 of 131 or 53.4% of 131). In terms of personal hygiene the analysis shows that 73 out of 131 students have a good level of hygiene, whilw 58 out of 131 students have a poor level of hygiene. There is a correlation between poor personal hygiene in students and video game addiction, where the students who correlate come from low socio-economic categories. Conclusion: The study’s findings from the statistical test (chi square) yielded a p value <0.05, indicating a substantial correlation between students personal hygiene to online games at istiqomah muhammadiyah vocation school 4 in samarinda